1991
DOI: 10.1111/j.1365-2222.1991.tb00802.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of a double‐blind dust‐mite avoidance trial with mite‐allergic rhinitic patients

Abstract: Inheritance and allergen exposure are key factors in the development and the course of atopic allergy, expressed as conjunctivitis, rhinitis, asthma or dermatitis. This study concerns the clinical significance of mite and mite-allergen avoidance measures based on intensive cleaning with acaricide (solidified benzylbenzoate) added (10 dwellings), and without biocidal activity (10 other homes) as a control in a double-blind trial with matched pairs. Twenty subjects with persisting rhinitic complaints were select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 18 publications
(21 reference statements)
2
33
0
1
Order By: Relevance
“…It is also clear that the application of air-cleaners alone will not be sufficient for effective reduction of exposure to indoor allergens, which is probably true, however, for most allergen avoidance measures [26][27][28]. In allergic asthmatic patients with a broad sensitization to inhalant allergens, a combination of different allergen reduction measures is generally necessary to obtain optimal improvement of clinical symptoms or airway parameters (PC20 histamine, peak flow variation, medication requirement).…”
Section: Discussionmentioning
confidence: 99%
“…It is also clear that the application of air-cleaners alone will not be sufficient for effective reduction of exposure to indoor allergens, which is probably true, however, for most allergen avoidance measures [26][27][28]. In allergic asthmatic patients with a broad sensitization to inhalant allergens, a combination of different allergen reduction measures is generally necessary to obtain optimal improvement of clinical symptoms or airway parameters (PC20 histamine, peak flow variation, medication requirement).…”
Section: Discussionmentioning
confidence: 99%
“…Of the six studies addressing this [135,136,140,[145][146][147], two contained no monitoring of allergens and cannot be interpreted in relationship to a reduction in allergen exposure [136,140]. Current recommendations are thus based on four studies, all of which reported benefit with a reduction in allergen exposure.…”
Section: Allergic Rhinitismentioning
confidence: 99%
“…Complete eradication of dust mites and their allergens is up to now impossible [77]. However, mite allergen concentrations can be reduced by a combination of methods using acaricides [78,79], with methods to separate mites from the sleeper by encasing mattresses, and further systems for decreasing humidity in the indoor environment [80]. Domestic pets, especially cats, are also a leading cause of asthma.…”
Section: The Role Of Allergens In Nonspecific Bronchial Hyperreactivimentioning
confidence: 99%